IMPLEMENTATION OF MONOPOLY MEDIA TO IMPROVE PANCASILA EDUCATION LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Liza; Tidi Maharani (Teaching and General Education Studies, 2026)
Pancasila education is essential for shaping students' character and citizenship values, yet many elementary students still experience low learning outcomes due to conventional and less engaging teaching methods. Therefore, innovative learning media are needed to support student understanding and motivation. This study aims to determine whether monopoly media can improve Pancasila education learning outcomes for third-grade students at SD Negeri 5 B Srikaton. This classroom action research (PTK) involved 20 third-grade students comprising 9 males and 11 females. The learning media applied is monopoly media. Data collection techniques include interviews, observations, tests, and documentation, while data analysis employed mixed-method approaches. The research was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The results showed significant improvement in Pancasila education learning outcomes. In Cycle I, student learning completeness increased from 30% (Pre-test) to 55% (Post-test). In Cycle II, learning completeness reached 85%. Based on these findings, it can be concluded that monopoly learning media is effective in improving Pancasila education learning outcomes for third-grade elementary school students. These findings imply that teachers should integrate game-based learning media to increase student engagement and mastery of Pancasila concepts. Future research may explore the use of monopoly media in other subjects and different grade levels to determine its broader applicability.